2002
DOI: 10.1093/humrep/17.8.1950
|View full text |Cite
|
Sign up to set email alerts
|

Should patients with polycystic ovarian syndrome be treated with metformin?: An enthusiastic endorsement

Abstract: Insulin resistance is a prominent feature of polycystic ovarian syndrome (PCOS), and women with the disorder are at increased risk for the development of other diseases that have been linked to insulin resistance-namely, type 2 diabetes and cardiovascular disease. This association between insulin resistance and PCOS must guide the chronic management of the disorder, and accumulating evidence suggests that administration of insulin-sensitizing drugs to individuals at high risk for type 2 diabetes decreases the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…24 Polycystic ovary syndrome, high BMI, and family history of diabetes have been associated with the development of GDM. 25,26 Our data strongly supported this association and showed that most (68.2%) of the cases of GDMþGIGT have at least one of risk factors for GDM. When we compared the GDM patients with and without risk factors, the two groups were similar with respect to age, gestational age at delivery, type of delivery, and birth weight .…”
Section: Discussionsupporting
confidence: 79%
“…24 Polycystic ovary syndrome, high BMI, and family history of diabetes have been associated with the development of GDM. 25,26 Our data strongly supported this association and showed that most (68.2%) of the cases of GDMþGIGT have at least one of risk factors for GDM. When we compared the GDM patients with and without risk factors, the two groups were similar with respect to age, gestational age at delivery, type of delivery, and birth weight .…”
Section: Discussionsupporting
confidence: 79%
“…Modifiable risk factors for CHD associated with PCOS include high total cholesterol and LDLC, high SBP and DBP, obesity, centripetal obesity, hyperglycemia and T2DM, insulin resistance, hyperinsulinemia, and the metabolic syndrome [4,8,11,13,14,[27][28][29][30]. In the current study, compared with healthy women originally recruited from a suburban Cincinnati school district, women with PCOS were much more likely to have higher BMI, waist circumference, total cholesterol, LDLC, triglyceride, SBP, DBP, insulin, glucose, and HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…Major CHD risk factors and insulin resistance associated with PCOS can, to a large extent, be ameliorated by diet and Glucophage (Bristol Myers Squibb, New York, NY) [8,[13][14][15]27,29,[45][46][47][48][49][50][51]. To prevent adverse CHD outcomes, diagnosis and recognition of PCOS should alert the clinician to identify and treat major CHD risk factors including dietdrug regimens designed to lower insulin and insulin resistance; to reduce BMI, triglyceride, LDLC, SBP, and DBP; and to raise HDLC.…”
Section: Discussionmentioning
confidence: 99%
“…By 1994 it represented up to 16% of new cases in urban areas, and by 1999, the incidence of new type 2 DM diagnoses ranged between 8% and 45%, depending on geographic location." Nestler [74] emphasized the capability of metformin in the primary prevention of DM in women with PCOS, concluding "…PCOS should be regarded as a general health issue and the use of insulin-sensitizing drugs such as metformin should be considered for prevention of type 2 diabetes." Nestler [74] also emphasized the use of insulin-sensitizing drugs in women with PCOS "…Women with PCOS are an insulin-resistant group with high prevalence of impaired glucose tolerance, who are at a markedly increased risk for type 2 diabetes.…”
Section: Primary Prevention Of Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Nestler [74] emphasized the capability of metformin in the primary prevention of DM in women with PCOS, concluding "…PCOS should be regarded as a general health issue and the use of insulin-sensitizing drugs such as metformin should be considered for prevention of type 2 diabetes." Nestler [74] also emphasized the use of insulin-sensitizing drugs in women with PCOS "…Women with PCOS are an insulin-resistant group with high prevalence of impaired glucose tolerance, who are at a markedly increased risk for type 2 diabetes. Therefore, it seems reasonable to presume that the demonstrated efficacy of insulin-sensitizing drugs-such as metformin-to stave off type 2 diabetes should apply to them as well."…”
Section: Primary Prevention Of Type 2 Diabetes Mellitusmentioning
confidence: 99%